Types of leaves preference by Kalophrynus palmatissimus in two forest reserves - Abdul Aziz, Muhammad Faris; Mohd. Top, Marina; Shohaimi, Shamarina; Ab Ghani, Nurul Izza; Fletcher, Christine (2019)
A collection of leaves was carried out at each captured area of Kalophrynus palmatissimus in Ayer Hitam Forest Reserve (AHFR), Selangor and Pasoh Forest Reserve (PFR), Negeri Sembilan. K. palmatissimus is a leaf litter frog. Leaves or leaf litter provide microhabitat structures for leaf litter frogs. Leaves or leaf litter offer retreat sites for leaf litter frogs and shelters for their food sources (i.e. diversity of invertebrates). However, there have been little discussions about the types of leaves as the microhabitat structure of K. palmatissimus. The objective of this study was to investigate the types of leaves that were highly adapted by K. palmatissimus at both forest reserves. Thirty four and thirty one quadrats (2m × 2m) were established in AHFR and PFR respectively for a collection of leaves. A total of 53 and 85 leaves were recorded at AHFR and PFR respectively. Most of the leaves that were collected at both forest reserves were non-hairy/smooth leaves. The data collections in AHFR and PFR have significantly contribute to better understanding of types of leaves as the most suitable habitat and foraging sites for K. palmatissimus.